2022
DOI: 10.1186/s13045-022-01335-y
|View full text |Cite
|
Sign up to set email alerts
|

Emerging strategies in targeting tumor-resident myeloid cells for cancer immunotherapy

Abstract: Immune checkpoint inhibitors targeting programmed cell death protein 1, programmed death-ligand 1, and cytotoxic T-lymphocyte-associated protein 4 provide deep and durable treatment responses which have revolutionized oncology. However, despite over 40% of cancer patients being eligible to receive immunotherapy, only 12% of patients gain benefit. A key to understanding what differentiates treatment response from non-response is better defining the role of the innate immune system in anti-tumor immunity and imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 432 publications
(501 reference statements)
0
34
0
Order By: Relevance
“…So far, there has been no breakthrough in the research of innate immune drugs regarding TLRs, and the selectivity and effectiveness are not clear yet. Emerging immunotherapies were proposed to overcome the primary and secondary resistance to existing immune checkpoint inhibitors, activate effector cells, and target immunosuppressive mechanisms in tumor microenvironment [141,[183][184][185]. More research needs to be explored regarding the mechanisms of the innate immune therapeutic agents.…”
Section: Conclusion and Prospectivementioning
confidence: 99%
“…So far, there has been no breakthrough in the research of innate immune drugs regarding TLRs, and the selectivity and effectiveness are not clear yet. Emerging immunotherapies were proposed to overcome the primary and secondary resistance to existing immune checkpoint inhibitors, activate effector cells, and target immunosuppressive mechanisms in tumor microenvironment [141,[183][184][185]. More research needs to be explored regarding the mechanisms of the innate immune therapeutic agents.…”
Section: Conclusion and Prospectivementioning
confidence: 99%
“…The composition of immune cells in the tumor microenvironment is an important predictor of bene cial survival and therapeutic outcome [41][42][43]. We found that TFPI2 expression was positively correlated with a variety of immune cells, such as CD8+T cells, B cells, cytotoxic cells and NK cells.…”
Section: Discussionmentioning
confidence: 81%
“…During the past decade, the explosive growth in macrophage-targeted therapy indicates that the TAM-targeted therapy is an effective antitumor strategy, especially as a complementary strategy in combination with conventional chemotherapy, radiotherapy, or immunotherapy. Most of the preclinical studies and clinical trials have been based on the therapeutic strategies according to their different mechanisms, including those that inhibit mononuclear macrophage recruitment, those that deplete TAMs, and those that reprogram TAMs [ 176 , 177 ]. However, clinical trials specifically designed to modulate or interfere with the self-renewal of TAMs are lacking.…”
Section: Discussionmentioning
confidence: 99%